(3GdLOhi GdEbJUGOjI ddeTQhYGJ GdESJKeGQjI hbjGS GdQHMjI GdJLGQjI hGdbhejIs - (3SejQ eMeO(B, (3YHO GdYRjR s ((3GdGScfOQjI(B:s (3ecJHI GdETYGY GdafjI(B,s, 2005)
(3GdOQGSI GdJaUjdjI ddQHMjI GdJLGQjI(B- (3JMdjd GdQHMjI GdbhejI ddeTQhY(B- (3OQGSGJ hMGdGJ JWHjbjIs
Keywords: (3GdESJKeGQs; (3GdeTQhYGJs; (3OQGSI GdLOhis